2021
DOI: 10.3390/foods10102439
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Based on 1H-NMR Reveal the Regulatory Mechanisms of Dietary Methionine Restriction on Splenic Metabolic Dysfunction in Obese Mice

Abstract: Methionine restriction (MR) has been reported to have many beneficial health effects, including stress resistance enhancement and lifespan extension. However, the effects of MR on the splenic metabolic dysfunction induced by obesity in mice remain unknown. This study aimed to investigate the scientific problem and clarify its possible mechanisms. C57BL/6J mice in the control group were fed a control diet (0.86% methionine, 4.2% fat) for 34 weeks, and others were fed a high-fat diet (0.86% methionine, 24% fat) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…Taken together, these results revealed that MRD significantly attenuated oxidative damage and inflammation in the thyroid of HCD mice. This finding is in agreement with that of our previous study showing that MRD improved oxidative stress and inflammation in the liver, brain, heart, spleen, and intestine of mice. ,,,, Oxidative stress and inflammation can inhibit iodine uptake and impair TH synthesis thus representing major contributors to thyroid dysfunction. , Previous studies showed that improving the oxidative stress and inflammation status can attenuate thyroid dysfunction . Therefore, we believe that MRD protected against thyroid dysfunction in HCD mice through improving redox state and inflammation in the thyroid.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Taken together, these results revealed that MRD significantly attenuated oxidative damage and inflammation in the thyroid of HCD mice. This finding is in agreement with that of our previous study showing that MRD improved oxidative stress and inflammation in the liver, brain, heart, spleen, and intestine of mice. ,,,, Oxidative stress and inflammation can inhibit iodine uptake and impair TH synthesis thus representing major contributors to thyroid dysfunction. , Previous studies showed that improving the oxidative stress and inflammation status can attenuate thyroid dysfunction . Therefore, we believe that MRD protected against thyroid dysfunction in HCD mice through improving redox state and inflammation in the thyroid.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in agreement with that of our previous study showing that MRD improved oxidative stress and inflammation in the liver, brain, heart, spleen, and intestine of mice. 41,42,45,54,89 Oxidative stress and inflammation can inhibit iodine uptake and impair TH synthesis thus representing major contributors to thyroid dysfunction. 40,90 Previous studies showed that improving the oxidative stress and inflammation status can attenuate thyroid dysfunction.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which MR ameliorates oxidative stress during CVD may be the activation of autophagy and hepatic H 2 S generation [ 85 , 124 ]. Activating transcription factor 4 (ATF4) is considered a master regulator of metabolism and is essential for the autophagy gene transcription program [ 125 ].…”
Section: Methionine Restriction (Mr) Aging and Diseasesmentioning
confidence: 99%
“…L-methionine is one of the eight essential amino acids that cannot be synthesized in human and animal bodies and is widely used in food, medicine, feed, and other industries [ 1 , 2 , 3 ]. However, L-methionine is still synthesized by chemical methods at present, and industrial microbial fermentation has not been realized [ 4 ].…”
Section: Introductionmentioning
confidence: 99%